Is Regionalism Simply a Diversion? : Evidence from the Evolution of the EC and EFTA - Bayoumi, Tamim (IMF Working Papers; Working Paper ;, 1995)
This paper considers the impact on trade of preferential arrangements in Europe since the 1950s. Using a first difference version of the gravity model, we find that the EEC and EFTA altered the pattern of international trade. We also find evidence of trade diversion in several cases, notably that of the EEC in the 1960s.